LIFE SATISFACTION OF OLDER ADULTS IN MANIPUR - Naorem, Indira Devi; MC, Arunkumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
It is anticipated that a number of elderly people will steadily rise as their quality of life improves in all areas. By making such improvements, people can benefit society instead of causing unneeded problems for their families and wider community. It is now one of most important objectives. As an essential aspect in determining life quality as well as successful ageing, life satisfaction is concentrated upon different studies since older adults are considered at risk in various ways, it has an impact on life satisfaction. “Life satisfaction” refers to well-being in areas such as contentment, tranquillity, self-assurance, etc. Stated differently, “life satisfaction” results from reflective, personal, along global judgement about what a human being considers they are and have done with their life. So, a person's life satisfaction becomes a concern as it influences well-being and maintaining relationships with society, especially for elderly people